Starburst Carbazole Derivatives as Efficient Hole Transporting Materials for Perovskite Solar Cells. Issue 1 (21st November 2021) - Jegorovė, Aistė; Truong, Minh Anh; Murdey, Richard; Daskeviciene, Maryte; Malinauskas, Tadas; Kantminiene, Kristina; Jankauskas, Vygintas; Getautis, Vytautas; Wakamiya, Atsushi
Abstract : Five new star‐shaped carbazole‐based molecules are successfully synthesized from low‐cost, commercially available reagents via a simple one‐step synthesis route. All carbazole derivatives comprise a 3, 6‐diaminocarbazole core with carbazole peripheral groups substituted at the 2‐ or 3‐positions and various aliphatic side chains. These molecules are evaluated as hole transporting materials to replace 2, 2′, 7, 7′‐tetrakis‐( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 9′‐spirobifluorene (spiro‐OMeTAD) in perovskite solar cells. Power conversion efficiencies of the devices with these carbazole hole transporting layers reach 19.0%, comparable with 19.7% obtained with the spiro‐OMeTAD‐based device. The thermal and operational stability of the candidate molecules are found to depend on the side chain substituents. Two candidate molecules with ethyl side chains show superior thermal stability compared with that of the reference solar cells prepared with spiro‐OMeTAD. Abstract : New starburst molecules, bearing the carbazole moiety both as a central core and as peripheral groups, are synthesized and evaluated as hole transporting materials for perovskite solar cells. Their power conversion efficiencies range from 16.3% to 19.0%. Compounds bearing short aliphatic chains show exceptionally high glass transition temperatures, resulting in superior thermal stability compared with that of spiro‐OMeTAD.